2021
DOI: 10.17718/tojde.961828
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Students’ Acceptance of Using Video Conferencing Tools in Distance Learning in Covid-19 Pandemic

Abstract: The outbreak of the COVID-19 pandemic has strongly influenced teaching and learning in Vietnam's higher education institutions. Social distancing -the health care practice of increasing the physical space between people to avoid spreading illness due to COVID-19 has required schools to employ distance learning. As such, video conferencing tools (VCTs) have been used nationwide to ensure effective responses to the requirement. Although teaching and learning with VCTs have been proven effective by many researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
3
20
0
2
Order By: Relevance
“…Third, the Perceived Ease of Use (PEOU) from Zoom cloud meetings does not significantly affect Acceptance Intention (AI) in accounting core courses or H3 is not accepted. This result is consistent with several previous studies that found no significant relationship between perceived ease of use and acceptance intention, such as the study from Han & Sa [35], and Nguyen et al [60]. According to Han & Sa [35] this pandemic case requires universities to implement new technology and revise the education delivery method.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Third, the Perceived Ease of Use (PEOU) from Zoom cloud meetings does not significantly affect Acceptance Intention (AI) in accounting core courses or H3 is not accepted. This result is consistent with several previous studies that found no significant relationship between perceived ease of use and acceptance intention, such as the study from Han & Sa [35], and Nguyen et al [60]. According to Han & Sa [35] this pandemic case requires universities to implement new technology and revise the education delivery method.…”
Section: Discussionsupporting
confidence: 91%
“…Fifth, Perceived Ease of Use (PEOU) affects significantly Zoom cloud meetings' Perceived Usefulness (PU) or H5 is accepted. This finding is in line with the original theoretical foundation of TAM and several previous studies that perceived ease of use affected perceived usefulness [52], [56]- [60]. According to Salloum et al [52], if students find it easy to use e-learning, its usefulness will also increase.…”
Section: Discussionsupporting
confidence: 88%
“…In order to achieve the best employable workforce possible, under the multiple considerations of the Ministry of Education and Training (MOET), education has been remarkably prioritized to ensure the highest educational quality. Therefore, while facing escalating effects as a result of the global health crisis-COVID-19it is essential for a growing line of research to focus attention on different levels of education and their use of SOL, including higher education (Ho et al, 2020;Le et al, 2021;Nguyen, 2021;Nguyen et al, 2020;Que, 2021;Vu, et al, 2020;Vu et al, 2022). Then, more educational and society-level policies can be designed to better fit the needs of diverse local contexts across the country, where learners hold a wide range of academic backgrounds, learning needs, and technological literacies .…”
Section: Related Studiesmentioning
confidence: 99%
“…The Covid-19 pandemic that broke out in early 2020 has become a global health emergency, leading to extraordinary socio-economic changes in every country in the world [1], including the educational system [2]. For Vietnamese education, this pandemic has made the education system face significant challenges in ensuring and maintaining educational activities while ensuring people's health.…”
Section: Introductionmentioning
confidence: 99%